Short stories for students. presenting analysis, context, and criticism on commonly studied short stories / Volume 25 - 4 0 16; Milne, Ira Mark.; 5 (Detroit : Thomson/Gale, 2007)
A guide to fourteen short stories for students, each including an introduction to the story and its author, a plot summary, character profiles, analysis of important themes, an explanation of literary technqiues and movements, and historical and critical essays.
Includes bibliographical references and indexes.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; History and criticism.;History and criticism. -- Short story;Short story.;Short story;Short story; 20; 2